This document discusses proving the Boolean logic problem B + A (B + C) + BC = B + AC. It first expands the brackets in the left side of the equation, then looks for common elements to combine like terms. After expanding and combining terms, it arrives at the right side of the equation, proving the identities are equal.
1 of 1
Download to read offline
More Related Content
Boolean Logic Example
1. Boolean Logic Problems
Prove that B + A (B + C) + BC = B + AC
B + A (B + C) + BC
First expand the brackets
B + AB + AC + BC
Now look for terms with common elements
B(1 + A ) + AC + BC But 1 + A = 1
B + AC + BC = B + BC + AC
Look for more terms with common elements
B(1 + C) + AC = B + AC